Exploring Transformative Relationships in a Virtual Learning Environment - JungEun Lee; Aliki Nicolaides (Adult Education Research Conference, 2014)
This study attempts to explore how transformative relationships take shape, and how they are fostered in the context of online learning environments. This knowledge will contribute to extending current understanding of quality of the relational conditions for cultivating transformative learning.